Ethephon induces monoterpene production and lipid oxidative stress in Houttuynia cordata Thunb - Xu, Y. Wen; Zhao, Dan; Husaini, Amjad M.; Guan, Ling Liang; Wu, Wei (2012)
Ethylene regulates many aspects of plant processes. Here we present the effect of application of ethephon (an ethylene-releasing compound) on the production of monoterpenes and induction of oxidative stress in Houttuynia cordata Thunb., a medicinal and aromatic herb rich in monoterpenes. H. cordata showed two peaks of total monoterpene content at 0.1 and 100 mM ethephon applications, after treatment with different concentrations of ethephon. However, high dose of ethephon (100 mM) also led to oxidative damage, as shown by increase in H 2 O 2 , malondialdehyde and antioxidative enzyme activities. Monoterpene accumulation at 100 mM ethephon is accompanied by oxidative stress and, hence, adverse to H. cordata, while 0.1 mM ethephon application is the most appropriate for enhanced monoterpene production.
Keywords: Medicinal plants; Plant morphology